New tools in nucleoside toolbox of tick-borne encephalitis virus reproduction inhibitors. Issue 5 (1st March 2017) - Orlov, Alexey A.; Drenichev, Mikhail S.; Oslovsky, Vladimir E.; Kurochkin, Nikolay N.; Solyev, Pavel N.; Kozlovskaya, Liubov I.; Palyulin, Vladimir A.; Karganova, Galina G.; Mikhailov, Sergey N.; Osolodkin, Dmitry I.
Graphical abstract: Abstract: Design and development of nucleoside analogs is an established strategy in the antiviral drug discovery field. Nevertheless, for many viruses the coverage of structure-activity relationships (SAR) in the nucleoside chemical space is not sufficient. Here we present the nucleoside SAR exploration for tick-borne encephalitis virus (TBEV), a member of Flavivirus genus. Promising antiviral activity may be achieved by introduction of large hydrophobic substituents in the position 6 of adenosine or bulky silyl groups to the position 5′. Introduction of methyls to the ribose moiety does not lead to inhibition of TBEV reproduction. Possible mechanisms of action of these nucleosides include the inhibition of viral entry or interaction with TBEV non-structural protein 5 methyltransferase or RNA-dependent RNA polymerase domains.